Studies On The Processing And Properties Of Conductive Single Fillers And Hybrid Fillers Filled Silicone Elastomer Composites - Kong, Kenneth Thean Soon (2012)
Multi-walled carbon nanotubes (MWCNTs) filled poly(dimethyl siloxane) (PDMS) composites were produced via two different processing methods. The first method is the solution mixing method where MWCNT were dispersed in a solvent using an ultrasonicator before mechanically mixed with PDMS. The second method entails the use of a mini-extruder to disperse and mix the MWCNTs and PDMS. Scanning Electron Microscopy (SEM) micrographs revealed that samples produced by mini-extruder exhibited shorter nanotubes, but better nanotubes dispersion compared with solution mixing. The composites prepared using the mini-extruder was found to have higher tensile strength and thermal conductivity. On the other hand, the composites prepared via solution mixing show higher electrical conductivity and better thermal stability. Functionalization of nanotubes with –OH and –COOH improves the tensile strength, thermal conductivity and thermal stability but does not contribute to the electrical conductivity enhancement. The properties of PDMS/exfoliated graphite nanoplatelet (xGnP) are comparable to that of PDMS/MWCNT. Composites filled with 4 wt% hybrid fillers with an xGnP/MWCNT-OH ratio of 3/1 show the highest thermal conductivity, electrical conductivity, and the lowest coefficient of thermal expansion. In general, the hybrid fillers can be used to produce composites with improved properties at lower cost due to the cheaper cost of xGnP.